The Integrated system for Natural Capital Accounting (INCA) in Europe: twelve lessons learned from empirical ecosystem service accounting - La Notte, A.; Vallecillo, S.; Grammatikopoulou, L.; Polce, C.; Rega, C.; Zulian, G.; Kakoulaki, G.; Grizzetti, B.; Ferrini, S.; Zurbaran-Nucc, M.; Bendito, E.; Vysna, V.; et al. (Pensoft Publishers, 2022)
The Integrated system for Natural Capital Accounting (INCA) was developed and supported by the European Commission to test and implement the System of integrated Environmental and Economic Accounting – Ecosystem Accounting (SEEA EA). Through the compilation of nine Ecosystem Services (ES) accounts, INCA can make available to any interested ecosystem accountant a number of lessons learned. Amongst the conceptual lessons learned, we can mention: (i) for accounting purposes, ES should be clustered according to the existence (or not) of a sustainability threshold; (ii) the assessment of ES flow results from the interaction of an ES potential and an ES demand; (iii) the ES demand can be spatially identified, but for an overarching environmental target, this is not possible; ES potential and ES demand could mis-match; (iv) because the demand remains unsatisfied; (v) because the ES is used above its sustainability threshold or (vi) because part of the potential flow is missed; (vii) there can be a cause-and-effect relationship between ecosystem condition and ES flow; (viii) ES accounts can complement the SEEA Central Framework accounts without overlapping or double counting. Amongst the methodological lessons learned, we can mention: (ix) already exiting ES assessments do not directly provide ES accounts, but will likely need some additional processing; (x) ES cannot be defined by default as intermediate; (xi) the ES remaining within ecosystems cannot be reported as final; (xii) the assessment and accounting of ES can be undertaken throughout a fast track approach or more demanding modelling procedures.